Studi Eksploratif Mengenai Kadar Garam Tradisional Di Kampung Garam Kabupaten Sikka - Agustina Sulastri; Kristina Tresia Leto; Kartini Rahman Nisa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to determine the levels of NaCl, to compare with the Indonesian National Standard and to see the influence of the environment and the cooking process on traditional salt produced by salt farmers in Kampung Garam, Sikka Regency. This research was conducted in Kampung Garam, Sikka Regency and the Mathematics and Natural Sciences Laboratory of the Muhamadiyah Maumere. The sample of this research is 3. The sampling technique used is purposive sampling. This study uses a qualitative exploratory method. After the data is collected, it is followed by data analysis, namely by data reduction, data presentation, triangulation and drawing conclusions. Based on the research results, the NaCl content in sample A was 90.38%, salt samples B and C were 85.71% and 79.37%. The process of making salt in Uneng City includes several stages: 1) preparation of raw salt raw materials; 2). coarse salt is transferred in a filter container poured with water; 3) this coarse salt drained water is collected in a bucket; 4) salt water is cooked in a container that has been prepared at 90°C; 5) after a few hours, salt crystals form; 6) and salt drying is done by filtering. Therefore, the results of the study concluded that the quality of salt was seen from the NaCl content produced from three locations in Salt Village, Sikka Regency using the evaporation method with the help of fuel heat according to (SNI 4435-2017) on the basis of dry weight (adbk) for sample A including quality K2 salt (medium quality), samples B and C belong to K3 salt quality (low quality) and there are environmental influences and the salt cooking process on production so that it is not suitable for consumption.